(untitled) (Universal International Scientific Journal, 2026)
In the course of the research, the mesoporous SiO₂ material was synthesized using the sol-gel method. The synthesis conditions — pH environment, temperature, reaction time, and saponin concentration — were optimized. The physicochemical and structural properties of the obtained materials were studied using modern analytical methods. In particular, the Brunauer–Emmett–Teller (BET) method was used to determine the surface area and pore parameters, X-ray diffraction (XRD) to evaluate the structure, and scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to determine the morphology. According to the results, the specific surface area of ​​the mesoporous SiO₂ was 801 m²/g, the total pore volume was 0.00105 cm³/g, and the average pore diameter was 2 nm. These indicators confirm that the material has high dispersion and adsorption properties